2014
DOI: 10.5468/ogs.2014.57.6.518
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous abortion and recurrent miscarriage: A comparison of cytogenetic diagnosis in 250 cases

Abstract: ObjectiveThe purpose of this study was to determine the frequency and distribution of cytogenetically abnormal miscarriages in couples with spontaneous abortions (SA) or recurrent miscarriages (RM).MethodsKaryotyping of specimens from 164 abortuses with SA and 86 abortuses with RM was successfully performed according to the standard cytogenetic methods using G-banding technique.ResultsAmong the total 164 cases of SA group, 81 (49.4%) were euploid and the rest (83, 50.6%) showed chromosomal abnormalities. In RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
50
0
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 29 publications
12
50
0
7
Order By: Relevance
“…Some authors did not find any statistically significant difference in the rates of cytogenetic abnormalities in abortions between couples with and those without RPL [15][16][17] . Others found that embryos with normal karyotypes were more common in RPL groups than in SA groups [18,19] , or, conversely, that cytogenetic abnormalities occurred more frequently in RPL groups than in SA groups [20] . Because of the limited sample sizes in most of these studies (ranging from 50 to 234 cases) and because of the inconsistency of the results obtained, our study aimed to compare the distribution of different types of chromosomal abnormalities in the largest study group to date (to the best of our knowledge) of miscarriages from couples with RPL and SA.…”
mentioning
confidence: 99%
“…Some authors did not find any statistically significant difference in the rates of cytogenetic abnormalities in abortions between couples with and those without RPL [15][16][17] . Others found that embryos with normal karyotypes were more common in RPL groups than in SA groups [18,19] , or, conversely, that cytogenetic abnormalities occurred more frequently in RPL groups than in SA groups [20] . Because of the limited sample sizes in most of these studies (ranging from 50 to 234 cases) and because of the inconsistency of the results obtained, our study aimed to compare the distribution of different types of chromosomal abnormalities in the largest study group to date (to the best of our knowledge) of miscarriages from couples with RPL and SA.…”
mentioning
confidence: 99%
“…RM etiologies of inherited thrombophilia in the literature there are conflicting studies about the possible role. There was a statistically significant correlation between the cytogenetic abnormalities with recurrent miscarriages reported in a study by Choi et al [7].…”
Section: Introductionmentioning
confidence: 73%
“…The frequency of genetic abnormalities depends on the developmental stage of pregnancy, maternal age and the number of previous miscarriages . In general, the earlier in gestation the pregnancy is lost, the more likely chromosomal abnormality will be detected . However, in recurrent pre‐embryonic pregnancy loss, especially in subfertile young women (under 35 years), genetic abnormalities are signifficantly less frequent (9.1–29.8%), which indicates a causative role of other factors …”
Section: Genetic Abnormalities In First Trimester Pregnancy Lossmentioning
confidence: 99%
“…Among the heterogeneous causes of miscarriage, chromosomal abnormalities, mainly aneuploidies, occur most frequently . Although in the great majority of cases they are de novo mutations and their impact on the risk in subsequent pregnancies is compound, identification of the cause of miscarriage plays an important role in genetic counseling …”
Section: Introductionmentioning
confidence: 99%